No inbreeding depression in laboratory‐reared individuals of the parasitoid wasp Allotropa burrelli. Issue 3 (15th January 2017) - Quaglietti, Bastien; Tamisier, Lucie; Groussier, Géraldine; Fleisch, Alexandre; Le Goff, Isabelle; Ris, Nicolas; Kreiter, Philippe; Fauvergue, Xavier; Malausa, Thibaut
Abstract: Inbreeding depression is a major concern in almost all human activities relating to plant and animal breeding. The biological control of pests with natural enemies is no exception, because populations of biocontrol agents experience a series of bottlenecks during importation, rearing, and introduction. A classical biological control program for the Comstock mealybug Pseudococcus comstocki (Hemiptera: Pseudococcidae) was initiated in France in 2008, based on the introduction of an exotic parasitoid, Allotropa burrelli Mues. (Hymenoptera: Platygastridae), a haplodiploid parasitoid imported from Japan. We evaluated the sensitivity of A. burrelli to inbreeding, to optimize rearing and release strategies. We compared several morphological and life‐history traits between the offspring of siblings and the offspring of unrelated parents. We took into account the low level of genetic variability due to the relatively small size of laboratory‐reared populations by contrasting two types of pedigree: one for individuals from a strain founded from a single field population, and the other generated by hybridizing individuals from two strains founded from two highly differentiated populations. Despite this careful design, we obtained no evidence for a negative impact of inbreeding on laboratory‐reared A. burrelli . We discussed the results in light of haplodiploid sex determination and parasitoid mating systems, and classical biological control practices. Abstract : Inbreeding depression is the biggest issue in reared populations, including biological control agents, and may lead to a decrease in production yield and even to population extinction. We assessed the risk of inbreeding depression in laboratory‐reared individuals of Allotropa burrelli, natural enemy of the Comstock mealybug, and found no evidence of major inbreeding depression.